Perancangan Sistem Informasi Retribusi Sampah untuk Meningkatkan Efisiensi dan Transparansi Pengelolaan Keuangan BUMDes - Fuji Alfiyah; Galih Widyatmojo (Fakultas Teknik Universitas Hamzanwadi, 2026)
The management of waste collection fees at the village level is still carried out manually, leading to various issues such as delayed billing, irregular record-keeping, and an increased likelihood of administrative errors. These conditions negatively affect the accuracy and effectiveness of financial reporting within the Village-Owned Enterprise (BUMDes). In response to these challenges, this study aims to develop a web-based waste collection fee information system design that is more structured, efficient, and user-friendly to enhance the accountability and transparency of village financial management. Data collection was conducted through interviews, observations, and literature studies to obtain a comprehensive understanding of system requirements. The system design employs the Unified Modeling Language (UML), which includes Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams, as well as database design using the Relational Database Model. In addition, this study produces user interface (UI) designs as initial representations of the system’s layout and interaction flow to support the operational needs of BUMDes. The findings indicate that the developed UML models, database design, and user interface prototypes can be used to address various limitations of the current manual system, particularly those related to data redundancy, inconsistent documentation, and difficulties in financial report preparation. In conclusion, this study emphasizes that all presented results are still in the design phase and are expected to serve as a foundational reference for the future implementation of a more modern, standardized waste collection fee information system that can be applied in BUMDes operations.